Implikasi Perbedaan Qira'at dalam Istinbath Hukum : Analisis Qira'at dari Segi Muthlaq dan Muqayyad - Basri Basri; Fikri Hamdani (LPPM IAIN Sultan Amai Gorontalo, 2020)
This article discusses the differences in qiraat in terms of mutlaq and muqayyad which lead to differences in istinbat Islamic law. Although qiraat is not the only basis for determining the law, it cannot be denied that the difference in qiraat has a major influence on the legal products which produced by the scholars. Using the descriptive-analytical method, this study discusses 3 verses in the Qur'an that have different qiraat which readings contain muqayyad on verses that are mutlaq, that, QS. al-Ba> qarah: 183-184 and QS. al-Ma>idah: 89 relating to the implementation of fasting, as well as QS. al-Ma> idah: 38 relating to the punishment of theft. From the study of the various qiraats found in the three verses, it can be understood that the existence of various qiraats that contain an insertion in the lafaz of a verse will cause the previous verse to have the status mutlaq to change to muqayyad. This difference in reading has led to the emergence of differences of opinion among scholars in establishing a law. Although some scholars say that the qiraat which is different from the Uthmani rasm is only an interpretation of a verse, it is even considered a syaz| qiraat.